Interaction of central angiotensin II and aldosterone on sodium intake and blood pressure - Gasparini, S. [UNESP]; Melo, M. R. [UNESP]; Nascimento, P. A. [UNESP]; Andrade-Franzé, G. M.F. [UNESP]; Antunes- Rodrigues, J.; Yosten, G. L.C.; Menani, J. V. [UNESP]; Samson, W. K.; Colombari, E. [UNESP] (Elsevier, 2019)
Recent studies demonstrated an important natriorexigenic mechanism activated by aldosterone acting in the hindbrain. Studies have also shown that aldosterone effects are intensified by angiotensin II (ANG II) and vice-versa. Thus, the aim of the present work was to test if angiotensinergic mechanisms in the forebrain are involved on sodium appetite to aldosterone infused into the 4th V and also if aldosterone into the 4th V might facilitate ingestive and cardiovascular responses to central ANG II. Male Holtzman rats with stainless steel cannulas implanted into the 4th ventricle (4th V) and lateral ventricle (LV) had access to 1.8% NaCl during 2 h/day. Chronic infusion of aldosterone (100 ng/h) into the 4th V for 7 days strongly increased 1.8% NaCl intake (16.1 ± 2.2 ml/2h/day). Losartan (AT1 receptor antagonist, 50 µg/1 µl) acutely injected into the LV reduced 1.8% NaCl intake induced by aldosterone infusion into the 4th V (8.8 ± 2.3 ml/2h/day). The pressor response to ANG II (50 ng/1 µl) into the LV increased in rats treated with aldosterone into the 4th V (45 ± 5 mmHg, vs. vehicle infusion: 26 ± 4 mmHg). Similarly, fluid intake (water + 1.8% NaCl) also increased when rats receiving aldosterone infusion were treated with ANG II acutely into the LV. These results suggest that forebrain angiotensinergic mechanisms are important for sodium intake produced by aldosterone acting in the hindbrain. In addition, aldosterone in the hindbrain produces sensitization of the central pressor mechanisms activated by ANG II acting in the forebrain.
Keywords: Aldosterone; Angiotensin; Arterial pressure; AT1 receptors; Sodium intake